Adaptive management in the context of barriers in European freshwater ecosystems. (15th December 2017) - Birnie-Gauvin, Kim; Tummers, Jeroen S.; Lucas, Martyn C.; Aarestrup, Kim
Abstract: Many natural habitats have been modified to accommodate for the presence of humans and their needs. Infrastructures – such as hydroelectric dams, weirs, culverts and bridges – are now a common occurrence in streams and rivers across the world. As a result, freshwater ecosystems have been altered extensively, affecting both biological and geomorphological components of the habitats. Many fish species rely on these freshwater ecosystems to complete their lifecycles, and the presence of barriers has been shown to reduce their ability to migrate and sustain healthy populations. In the long run, barriers may have severe repercussions on population densities and dynamics of aquatic animal species. There is currently an urgent need to address these issues with adequate conservation approaches. Adaptive management provides a relevant approach to managing barriers in freshwater ecosystems as it addresses the uncertainties of dealing with natural systems, and accommodates for future unexpected events, though this approach may not be suitable in all instances. A literature search on this subject yielded virtually no output. Hence, we propose a step-by-step guide for implementing adaptive management, which could be used to manage freshwater barriers.